A democratic city? The impact of public transport networks on social cohesion - Makhubu, Absalom (International Planning History Society Proceedings, 2016)
Urbanity is political. Thus, urbanists have to engage with political issues and systems in order to address injustices of the past, and create a more equitable present. Especially in the context of South African cities, which are still dominated by apartheid morphologies. 2016 marks South Africa’s 22nd year into democracy, but what are the achievements and advancements in transforming the spatial legacy the ‘new’ country inherited from the Apartheid dispensation? Moreover, what are the characteristics of a post-apartheid, democratic city and society? The City of Johannesburg, the local authority of the Johannesburg Metropolitan regions, believes that transport networks must play a role to support the creation of social cohesion in a highly segregated city to address the spatial legacy of apartheid. It has therefore implemented a number of transport oriented development plans throughout the city including the Corridors of Freedom development plan. This paper unpacks theory around the concept of social cohesion, in order to understand why this is relevant to planning trajectories in South Africa. Furthermore, it discusses social, economic and spatial legacies to which planning needs to respond. It examines the Corridors of Freedom, a ‘Transit Orientated Development’ framework proposed by the City of Johannesburg aimed at “stitching” the city together. It critically analyses the plan’s objectives and how it addresses issues of social cohesion to highlight some of the strengths and shortcomings of the proposed ‘Corridors’.